SOCIAL ESSENCE OF THE ACTIVITIES OF EMPLOYEES OF INTERNAL AFFAIRS OF UZBEKISTAN(PHILOSOPHICAL ANALYSIS) - Dadakhanov Shavkat Shakirovich (Research Focus International Scientific Journal, 2025)
The article analyzes the social essence of the employees of the internal affairs of Uzbekistan from a philosophical point of view. The purpose of the study is to determine the place of persons serving in the internal affairs bodies in society, the philosophical foundations of their legal-protective and social stability functions. The article uses dialectical - materialistic and phenomenological methods, integrating the commentator and theoretical approaches of Law, Ethics and political science. In the process of analysis, the interaction of internal affairs personnel with society, the boundaries of social contract, powers and responsibility formed on their basis, and the princip.